1991
DOI: 10.1042/bj2760493
|View full text |Cite
|
Sign up to set email alerts
|

Differential internalization and processing of atrial-natriuretic-factor B and C receptor in PC12 cells

Abstract: PC12 cells express two atrial-natriuretic-factor-(ANF)-receptor subtypes with molecular masses of 130,000 (B receptor) and 70,000 (C receptor). The B-receptor subtype constitutes 65% of the cell-surface receptor population, and the remaining 35% are C receptors as determined by saturation binding studies in the presence of C-ANF, a C-receptor-selective analogue. ANF-(99-126)-peptide [ANF(99-126)], which can bind to both B- and C-receptor subtypes, was rapidly internalized into the cells after incubation at 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…These results fit to the kinetics of the VILIP-1 effect on GC activity (this study) and the observed receptor half-life during desensitization of the related receptor GC-A (Pandey et al, 2002). Moreover, a very similar effect of monesin on the recycling of GC-A, where monensin blocked the reappearance of internalized receptors on the cell surface, was described in PC12 cells (Rathinavelu and Isom, 1991).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These results fit to the kinetics of the VILIP-1 effect on GC activity (this study) and the observed receptor half-life during desensitization of the related receptor GC-A (Pandey et al, 2002). Moreover, a very similar effect of monesin on the recycling of GC-A, where monensin blocked the reappearance of internalized receptors on the cell surface, was described in PC12 cells (Rathinavelu and Isom, 1991).…”
Section: Discussionsupporting
confidence: 60%
“…It has been previously shown that a desensitization-dependent internalization of GC-A occurs (Rathinavelu and Isom, 1991) and that the reduction of surface expression of GC-A reaches a maximum level approximately 15-20 minutes after receptor stimulation (Pandey et al, 2002). By contrast, at this time point the receptor response is not desensitized in VILIP-1-transfected cells, but a rather strong increase in cGMP accumulation can be noticed compared with non-transfected cells (Fig.…”
Section: Expression Of Vilip-1 Increases the Surface Expression Of Gcmentioning
confidence: 79%
“…However, in the ligand-binding domain, very little similarity is observed, and this is reflected in the lack of interaction of ligands amongst various members of the guanylyl cyclase receptor family. The pH-dependent binding that we report in this study for the ST receptor is in direct contrast to the atrial natriuretic factor receptor where low pH actually induces rapid dissociation of the ligand [38]. When one considers the marginally acidic microenvironment of the small intestine, it is apparent that ST has exploited this in its interactions with the receptor.…”
Section: Discussionmentioning
confidence: 67%
“…510 " 13 Two distinct types of receptors have been identified. One type of receptor is a particulate guanylate cyclase 14 and is designated as the biologically active receptor.…”
mentioning
confidence: 99%